1995
DOI: 10.1093/carcin/16.11.2847
|View full text |Cite
|
Sign up to set email alerts
|

Refractoriness to mammary tumorigenesis in parous rats: is it caused by persistent changes in the hormonal environment or permanent biochemical alterations in the mammary epithelia?

Abstract: Administration of a single i.v. injection of 50 mg N-methyl-N-nitrosourea (MNU)/kg body wt to 50- to 60-day old virgin rats, 120-day-old virgin rats, and 120-day-old parous rats (Sprague-Dawley; n = 18-37) resulted in a high incidence of mammary carcinomas in the virgin animals (97.3% in 50- to 60-day-old virgin rats; 75.0% in 120-day-old virgin rats), but mammary carcinomas did not develop in the parous rats. The concentrations in serum of various mammotropic hormones were measured in identical groups of rats… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

13
100
1

Year Published

2001
2001
2010
2010

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 110 publications
(114 citation statements)
references
References 0 publications
13
100
1
Order By: Relevance
“…Furthermore, this trend was not observed in the p53 þ /À mice without a transgene. Although parity appears to reduce the risk of mammary carcinoma in the p53 þ /À mice without the transgene, in agreement with expectations from studies in rodents and humans (Moon, 1969;Swanson et al, 1995;Thordarson et al, 1995;Hamilton and Mack, 2003), this protection was negated in T380A mice and dramatically reversed in p53 þ /À T380A mice.…”
Section: Resultssupporting
confidence: 87%
See 1 more Smart Citation
“…Furthermore, this trend was not observed in the p53 þ /À mice without a transgene. Although parity appears to reduce the risk of mammary carcinoma in the p53 þ /À mice without the transgene, in agreement with expectations from studies in rodents and humans (Moon, 1969;Swanson et al, 1995;Thordarson et al, 1995;Hamilton and Mack, 2003), this protection was negated in T380A mice and dramatically reversed in p53 þ /À T380A mice.…”
Section: Resultssupporting
confidence: 87%
“…Parity is known to modulate the risk of mammary tumorigenesis in both humans and rodents (Moon, 1969;Thordarson et al, 1995;Hamilton and Mack, 2003). In mice, it has been demonstrated that parity protects against mammary carcinogenic insult and that the effects of the carcinogen are dependent upon the mitogenic environment at the time of insult; the beneficial effect of parity is reversed by prolactin stimulation from pituitary isografts.…”
Section: Discussionmentioning
confidence: 99%
“…If the ERα-positive cell population is reduced, the number of cell divisions driven by estrogen and the potential development and progression of cancer should be reduced. A decrease in ERα expression after pregnancy has been described in animal models, and in the human breast, there is immunohistochemical evidence for decreased ERα expression in undifferentiated breast lobules that are associated with the nulliparous state (40,41). However, the observation, on the mRNA level, that this reduction occurs soon after pregnancy and that it persists is novel.…”
Section: Discussionmentioning
confidence: 96%
“…In particular, there is strong epidemiological evidence that women who experience a full-term pregnancy early in their lives have a significantly reduced risk for developing breast cancer (3)(4)(5). This is recapitulated in rat models that demonstrate that early full-term pregnancy confers resistance to chemical carcinogen-induced mammary tumorigenesis (6)(7)(8)(9)(10)(11). This protection can be mimicked with the hormones estrogen (E) and progesterone (P; refs.…”
mentioning
confidence: 99%
“…The utility of the rodent models in which a defined hormonal regimen can be used to mimic the protective effect of pregnancy is well documented (9)(10)(11)(12)(13)(14)(15)(16)(17).…”
mentioning
confidence: 99%